Using the diverse vegetables as a filtration plants in aquaculture intensive system - Hassan, Sadam M.; Rashid, Muna Salah; Albassam, Nuha Hameed; Madlul, Najlaa Salah; Muhaimeed, Ahmed R.; Sulaiman, Muhammad Aliyu (Tikrit University, 2025)
Changes to the physico-chemical conditions of treated water affect the biological traits of the aquatic organisms. There are water quality issues in rearing fish using a recirculating aquaculture system. Certain technologies for water treatment to improve its quality are highly energy intensive and expensive to use, thus implying high investment and operating costs. There is needed to look for novel method of water treatment which not only improves water quality and fish growth performance but is also cost effective and energy efficient to face climate change, lack of rain, and consequently fresh water scarcity, especially in the countries most affected in the Middle East. Any improvement by incorporating the mechanical and biological filter in one unit of an aquaponics intensive system is important in order to improve its efficiency and aquaculture yield. By incorporating a plant, namely: strawberry, peppermint, cucumber, and okra as a biological filtration to absorb the nutrient disintegrated additional to the green sponge layer and gravel as a mechanical filtration even for control treatment, aquaculture may become more sustainable in the future. After the acclimation interval, 24 tanks were stocked with 7 fish of an average initial weight of 15.74g. However, treatments were assigned to each container at random to make five treatments. First, this work evaluated the gravel fine mesh was used in the control treatment, strawberry, peppermint, cucumber, and okra, as a biofilter media in an aquaponics system. The results showed a significant effect on common carp average growth performance for cucumber and okra compared to the control treatment. However, a better growth performance for common carp culture in water-exposed cucumber and okra demonstrated significant improvement of FCR. Hence, improve in fish productivity in aquaponics system. There is a significant effect on cell counts and plasma enzyme and biochemistry conditions in strawberry, peppermint, cucumber, and okra biofilter medias. The liver cells and gills of the fishes grown in strawberry, peppermint, cucumber, and okra exhibited a normal sinusoid organisation with no indications of lesions or abnormalities of the hepatocytes. In briefly, the study elucidates the interests of using strawberry, peppermint, cucumber, and okra as a biofilter unit for aquaculture due to improved growth performance of common carp fish.